I Can’t Work It Out! Maths Anxiety and Discount Effectiveness - Xu, Xiaoqi (Auckland University of Technology, 2021)
Mathematics Anxiety (MX) and Mathematics Ability (MA) are separate variables, that do not necessarily correlate (Suri, Monroe and Koc, 2013). Whereas MA is learned, MX is apparently innate; a person with a high mathematical ability can still suffer mathematical anxiety and vice versa. Suri et al show that in the USA both high levels of MX and low levels of MA tend to lead consumers to prefer a discount framed simply as a price reduction rather than a percentage reduction. The purpose of this thesis is first, to see if this concept (regarding the relationship of maths anxiety and ability) holds true cross-culturally; to explore the relationship between maths anxiety, maths ability and purchase intentions when exposed to a discounted product. There is good reason to suppose that Chinese consumers process information differently to their American counterparts, and they certainly have enjoyed a different educational experience. Second, the analysis is conducted using two different discount frames; one a simple monetary reduction and the other a more complex percentage reduction. Minor hypotheses and propositions concerning possible gender and age cohort differences in this regard will also be developed and tested. The research is conducted using panel data drawn from the United States and China. The scales are developed and tested, then analysis by simple means difference testing and Hayes PROCESS models to address the hypotheses is conducted.
Keywords: Maths Anxiety; Maths ability; Price discount; Purchase intention; Cross-cultural; Age; Gender